Comprehensive analysis of the prognostic and immunotherapeutic implications of STAT family members in human colorectal cancer - Li, Dingchang; Jiao, Yanan; Gao, Wenxing; Hu, Shidong; Li, Dingling; Zhao, Wen; Chen, Peng; Jin, Lujia; Zhao, Yingjie; Ma, Zhaofu; Wu, Xiansheng; Yan, Yang; et al. (Frontiers in Genetics, 2022)
Background: Colorectal cancer (CRC) is the third most prevalent cancer worldwide and the second leading cause of cancer mortality. Signal transducer and activator of transcription (STAT) proteins are a group of transcription factors implicated in cell signal transduction and gene transcription in several cancer types. However, the level of expression, genetic alterations, and biological function of different STATs, as well as their prognostic and immunotherapeutic value in CRC remain unclear. Methods: The mRNA and protein expression levels, genetic alterations, prognostic value, gene–gene and protein–protein interaction networks, and biological function of STATs in CRC were studied using the GEPIA, HPA, cBioPortal, PrognoScan, Kaplan–Meier plotter, GeneMANIA, STRING, and Metascape databases. The expression of STATs in CRC was confirmed using immunohistochemistry (IHC). Finally, the relationship between STAT expression and immune infiltration as well as immunotherapy-associated indicators was also investigated. Results: The expression levels of STAT2/5A/5B are downregulated in CRC, and the STAT1/3/4/5B expressions were significantly associated with the tumor stage of patients with CRC. The abnormal expression of STAT2/4/5B in patients with CRC is related to the prognosis of patients with CRC. The STATs and their neighboring proteins are primarily associated with lymphocyte activation, cytokine-mediated signaling pathways, positive regulation of immune response, regulation of cytokine production, and growth hormone receptor signaling pathways in cancer. The expression of STATs was significantly associated with immune infiltration and immunotherapy response-associated indicators. Conclusion: This study may help further understand the molecular mechanism of CRC and provide new prognostic biomarkers and immunotherapy targets in patients with CRC.